Ultrasound-guided erector spinae plane block in patients undergoing pediatric abdominal surgery: a randomized study - Parvin Pınar; Serdar Yeşiltaş; Meltem Türkay; Kazım Karaaslan; Ayda Türköz (Ain Shams Journal of Anesthesiology, 2022)
Abstract Background Erector spinae plane block (ESPB) can provide effective analgesia in pediatric abdominal surgery. Additionally, when used as an analgesic method in abdominal surgery, ESPB may increase regional intra-abdominal tissue oxygen saturation (rSO2) throughout the operation. However, the number of related studies conducted on pediatric patients is insufficient. Results Fifty-two patients undergoing lower abdominal surgery were allocated into two groups, the ESPB (E) and the control (C). Group E received general anesthesia plus unilateral ultrasound-guided ESPB, and group C received general anesthesia alone. Intraoperative fentanyl consumption, Face, Legs, Activity, Cry, Consolability (FLACC) score, time to first rescue analgesia and adverse events were recorded over the first 24 h postoperatively. The rSO2 level was evaluated in both groups throughout the operation. The FLACC score was significantly lower in group E than in group C (p<0.05). Four patients in group E required intraoperative fentanyl compared to 12 patients in group C (p<0.05). The first rescue analgesic administration time was significantly longer in group E than in group C (p<0.05). No significant difference in rSO2 values was detected between the groups (p>0.05). However, in group E, rSO2 values were significantly increased after the block compared to the postinduction values. Conclusions ESPB provides effective perioperative analgesia in children undergoing low abdominal surgery. Although there was no significant difference in rSO2 values between the groups, ESPB administration consistently increases rSO2 over time. Trial registration The trial was registered at ClinicalTrials.gov before patient enrolment ( NCT03808129 -13.12.2018).